Nanostructured Colloidal Particles by Confined Self-Assembly of Block Copolymers in Evaporative Droplets - Kim, Minsoo P.; Yi, Gi-Ra (Frontiers in Materials, 2015)
Block copolymers (BCPs) can create various morphology by self-assembly in bulk or film. Recently, using BCPs in confined geometries such as thin film (one-dimension), cylindrical template (two-dimension), or emulsion droplet (three-dimension), nanostructured BCP particles have been prepared, in which unique nanostructures of the BCP are formed via solvent annealing process and can be controlled depending on molecular weight ratio and interaction parameter of the BCPs, and droplet size. Moreover, by tuning interfacial property of the BCP particles, anisotropic particles with unique nanostructures have been prepared. Furthermore, for practical application such as drug delivery system, sensor, self-healing, metamaterial, and optoelectronic device, functional nanoparticles can be incorporated inside BCP particles. In this article, we summarize recent progress on the production of structured BCP particles and composite particles with metallic nanoparticles.